A fully fused non-fullerene acceptor containing angular-shaped S, N-heteroacene and perylene diimide for additive-free organic solar cells. (8th August 2019) - Li, Zhaoning; Wang, Jungan; Huang, Hongyan; Liu, You; Yun, Yikai; Cheng, Zhengchun; Liu, Shuli; Ding, Zhucheng; Zhao, Baomin; Huang, Wei
Abstract : A fully fused small molecule acceptor containing angular-shaped S, N -heteroacene and perylene diimide was synthesized and employed as a non-fullerene acceptor for additive-free organic solar cells. Abstract : Constructing fused perylene diimide (PDI) dimers with heteroaromatic bridges toward non-fullerene acceptors (NFAs) has become an efficient strategy to achieve high performance organic solar cells (OSCs). Here, FDTC-PDI containing fully fused two PDIs with one central unit of angular-shaped S, N -heteroacene was developed and explored as a novel NFA for OSCs. The molecular geometry, optical spectra, energy levels, charge carrier mobilities and the morphology discrepancies as well as the corresponding photovoltaic performance ofFDTC-PDI and its non-fused precursor, DTC-PDI, were investigated and compared. Theoretical calculations reveal thatFDTC-PDI has a better planar molecular conformation and more effective conjugated length thanDTC-PDI . As a consequence, by blendingFDTC-PDI withPTB7-Th as the electron acceptor and the electron donor material, respectively, the inverted solar cells exhibited an encouraging PCE of 4.78% along with a J sc of 11.72 mA cm −2, a V oc of 0.96 V and a FF of 42.5%, which were superior to those of its counterpartDTC-PDI (2.68%). These results are associated with the higher molar extinction coefficient, more balanced carrier mobility and better morphology ofFDTC-PDI as well as its high-lying LUMO energy level. Note that no solvent additive was used in the process of device optimizations, thus simplifying the device fabrication, and improving the stability and reproducibility of the photovoltaic devices. We also prospect much broader application of the angular-shaped S, N -heteroacene with rigidity and planarity as a promising building block for fully fused electron acceptors for accomplishing the challenges in organic solar cells.